Electromagnetic scattering between an elliptically inhomogeneous plane wave and a multilayered cylinder. Issue 18 (11th December 2020) - Dinia, L.; Mangini, F.; Frezza, F.
Abstract : The interaction of a stratified cylinder with an elliptically inhomogeneous plane wave is introduced and also determined through a rigorous theoretical approach. The scattered electromagnetic field by a multilayered cylinder is investigated through an application of the generalized Vector Cylinder Harmonics (VCH) expansion. The exact mathematical model to represent this scenario considers the so-called complex-angle formalism reaching a superposition of Vectorial Cylindrical-Harmonics and the T-matrix formulation to contemplate the multi-scattering process between the cylinders. The validation of the procedure was accomplished with a comparison between the numerical results obtained with the Finite Element Method (FEM) in Comsol Multiphysics environment and a homemade Matlab code.